Evidence and age estimation of mass wasting at the distal lobe of the Congo deep-sea fan. (August 2017) - Croguennec, Claire; Ruffine, Livio; Dennielou, Bernard; Baudin, François; Caprais, Jean-Claude; Guyader, Vivien; Bayon, Germain; Brandily, Christophe; Le Bruchec, Julie; Bollinger, Claire; Germain, Yoan; Droz, Laurence; et al.
Abstract: On continental margins, sulfate reduction occurs within the sedimentary column. It is coupled with the degradation of organic matter and the anaerobic oxidation of methane. These processes may be significantly disturbed by sedimentary events, leading to transient state profiles for the involved chemical species. Yet, little is known about the impact of turbidity currents and mass wasting on the migration of chemical species and the redox reactions in which they are involved. Due to its connection to the River, the Congo deep-sea fan continuously receives huge amount of organic matter-rich sediments primarily transported by turbidity currents, which impact on the development of the associated ecosystems (Rabouille et al., 2017 ). Thus, it is well suited to better understand causal relationships between sedimentary events and fluid flow path, with consequences on the zonation of early diagenesis sequences. Here, we combined sedimentological observations with geochemical analyses of pore-water and sediment samples to explore how sedimentary instabilities affected the migration of methane and the distribution of organic matter within the sedimentary column. The results unveiled mass wasting processes affecting recent turbiditic and pelagic deposits, and are interpreted as being slides/ slumps and debrites. Two slides were responsible for the exhumation of an organic matter-rich sedimentary block of more than 5 m thick and the movement of a methane-rich sedimentary block, while turbidity currents enable the intercalation of sandy intervals within a pelagic clay layer. The youngest slide promoted the development of two Sulfate Methane Transition Zones (SMTZ), and may have possibly triggered a lateral migration of methane. Numerical simulation of the sulfate profile indicates that the youngest sedimentary event has occurred around a century ago. Our study emphasizes that turbidity currents and sedimentary instabilities can significantly affect the transport paths and the distribution of both methane and organic matter in the terminal lobe complex, with consequences on geochemical zonation of the sequential early diagenetic processes within the sedimentary column.